Our Journey Together - Trump, Donald, 1946- ([United States] : Winning Team Publishing, 2021)
Photobook covering President Donald J. Trump's time in the White House. Photographs and captions handpicked by the President.
New Book 2022 Summer.
Keywords: Trump, Donald, -- 1946- -- Pictorial works; Presidents -- United States -- Pictorial works; Politics and government; Photobooks; United States -- Politics and government -- 2017-2021 -- Pictorial works; Photobooks